2017
DOI: 10.1186/s13071-017-2538-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic expression of cytokine and transcription factor genes during experimental Fasciola gigantica infection in buffaloes

Abstract: BackgroundDetermining the mechanisms involved in the immune-pathogenesis of the tropical liver fluke, Fasciola gigantica, is crucial to the development of any effective therapeutic intervention. Here, we examined the differential gene expression of cytokines and transcription factors in the liver of F. gigantica-infected buffaloes, over the course of infection.MethodsWater buffaloes (swamp type) were infected orally with 500 F. gigantica encysted metacercariae. Liver tissue samples were collected 3, 10, 28, 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 62 publications
7
29
0
Order By: Relevance
“…In the course of our previous research, a modest Th2 response at the early stage of infection was found to balance harmful Th1 and Th17 responses in F. gigantica -infected buffaloes [ 46 ]. We also observed that F. gigantica infection had a significant impact on the expression of Th1, Th2, Th17, and Treg cytokines [ 47 ]. IL-17 is important in the host defense against extracellular pathogens, predominantly at mucosal sites.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of our previous research, a modest Th2 response at the early stage of infection was found to balance harmful Th1 and Th17 responses in F. gigantica -infected buffaloes [ 46 ]. We also observed that F. gigantica infection had a significant impact on the expression of Th1, Th2, Th17, and Treg cytokines [ 47 ]. IL-17 is important in the host defense against extracellular pathogens, predominantly at mucosal sites.…”
Section: Discussionmentioning
confidence: 99%
“…The affected cells will increase the releasing of IL-13 that act as a trigger to T-helper 2 lymphocytes to overcome the continuous irritation (20). With time the lesions caused by Fasciola spp were increased in severity, this occurs due to increase in the level of tumor growth factor -beta (TGF-β) which cause immunosuppression of host defenses to facilitate parasite colonization (21).…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that rFg14-3-3e protein suppresses immune response is in line with what we described previously during F. gigantica infection in buffaloes. An ‘early’ TGF-β-associated immuno-suppressive response together with upregulation of liver IL-10 mRNA expression [ 52 ] and increased level of serum IL-10 cytokine [ 53 ] have been observed in buffaloes during early F. gigantica infection. In another study, we reported downregulation of MHC-II related genes and suppression of the host pro-inflammatory (Th1) immune response during early F. gigantica infection in buffalo liver [ 54 ].…”
Section: Discussionmentioning
confidence: 99%